1996
DOI: 10.1074/jbc.271.32.19298
|View full text |Cite
|
Sign up to set email alerts
|

Mode of Action of the Antimicrobial Peptide Indolicidin

Abstract: Indolicidin is a cationic antimicrobial peptide isolated from bovine neutrophils. It consists of only 13 amino acids, has the highest tryptophan content of any known protein, and is amidated at the carboxyl terminus in nature. By circular dichroism spectroscopy a weak poly-L-proline II extended helix structure was observed that became substantially more pronounced upon interaction with liposomes. Indolicidin bound purified surface lipopolysaccharide with high affinity and permeabilized the outer membrane of Es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
311
2
4

Year Published

1998
1998
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 428 publications
(334 citation statements)
references
References 43 publications
17
311
2
4
Order By: Relevance
“…To determine the underlying mechanism, many studies analyzed the activities of diastereomers that possess an amphipathic structure, assuming that they play similar roles as native AMPs composed by L-amino acids only (Zasloff, 1987;Mor et al, 1991;Falla et al, 1996;Shai and Oren, 1996).…”
Section: Helicitymentioning
confidence: 99%
See 1 more Smart Citation
“…To determine the underlying mechanism, many studies analyzed the activities of diastereomers that possess an amphipathic structure, assuming that they play similar roles as native AMPs composed by L-amino acids only (Zasloff, 1987;Mor et al, 1991;Falla et al, 1996;Shai and Oren, 1996).…”
Section: Helicitymentioning
confidence: 99%
“…Amidation of the C-terminal carboxyl increases antimicrobial activity It has been shown that amidation of the C-terminal carboxyl group is able to improve the antimicrobial activity of AMPs (Falla et al, 1996;Oren and Shai, 1996;Jia et al, 2000;Konno et al, 2007). When the structures of the AMP dermaseptin S3 and its amidated analog were compared, Shalev et al found that the amidated dermaseptin has an induced and/or stabilized α-helical conformation, and thus, is more rigid and extended than the nonamidated analog (Shalev et al, 2002).…”
Section: Part IImentioning
confidence: 99%
“…This process is followed by inhibition of intracellular processes, such as protein synthesis [45], DNA replication [46], or by targeting mitochondria and causing efflux of ATP [5]. Support for these mechanisms of action comes from investigations of BUF [46], histatins [47], the P-rich antimicrobial peptide indolicidin [48], and others [4].…”
Section: Alternative Mechanisms Of Actionmentioning
confidence: 99%
“…The fourth group comprises extended peptides with one or two amino acids predominating [7][8][9] . Well characterized antimicrobial peptides have a size varying from 30 to over 100 residues and consist of a wide range of different amino acids 10 . The mode of action of these peptides can be categorized into two mechanisms: transmembrane pore-forming mechanisms and modes of intracellular killing 11,12 .…”
Section: Introductionmentioning
confidence: 99%